Study on the Kinematics and Dynamics Simulation of Helical Gear Limited Slip Differential - Liu Xiaoyong; Wang Haoren; Cui Gaojian; Li Shaosong; Ren Haibo; Tu Yongfa (Jixie chuandong)
Three-dimension solid model of helical gear limited slip differential is built by using CATIA,and then the virtual prototype model is established through importing the 3D solid model into ADAMS/View. In the virtual environment,based on the kinematics dynamics simulation and analysis with two different typical work conditions,including straight-line driving on good pavement and double tire-road friction coefficients,the torque curve,the force and angular velocity curves of helical gear of limited slip differential are acquired.By comparing with theoretical calculations values,the correctness of model and the effectiveness of simulation method are verified. The study results provide the basis for the dynamic optimization and fatigue life prediction of the helical gear limited slip differential.